Design, analysis and application of novel variable flux memory machines for energy-efficient traction electrification - Yan, Yuming (Nanyang Technological University, 2024)
With increasing concerns about environmental protection and sustainable development, energy-efficient traction electrification has drawn increasing attention recently. Electric machines intended for propulsion, serving as the fundamental technology for traction electrification, are anticipated to feature exceptional efficiency, potent field-weakening capabilities, impressive torque/power density, robust mechanical integrity, and strong cost-effectiveness. Among various electric machines for traction electrification, permanent-magnet (PM) machines exhibit promising merits of excellent torque capability, high power density and high efficiency with the adoption of rare-earth PM. However, PM machines suffer from poor field weakening capability, which is critical for traction machines due to frequent start-stop, frequent acceleration or deceleration, climbing and high-speed cruise. Broadly speaking, in order to attain an extensive operational spectrum, an opposing d-axis current is introduced to offset the influence of the permanent magnet magnetic field. Nevertheless, due to the voltage and current rating limitations of inverters, this extension of speed range is limited and the efficiency is reduced accordingly. To improve the situation, hybrid-excited machines, which employ an extra set of winding to regulate the air-gap flux, have gained some attentions. It is found improved flux regulation capability can be obtained for hybrid-excited machines, but this machine type suffers from low efficiency due to considerable copper losses that restrict its industrialization in traction applications. In this research work collaborated with Rolls-Royce (Singapore) Pte. Ltd., extensive investigations are conducted regarding the emerging variable flux memory (VFM) machines, known for their remarkable torque density and advanced flux regulation capability to facilitate their industrial traction electrification applications. The performance attributes of a range of electric machines are reviewed in Chapter 2 to evaluate their potential for traction electrification. Among conventional electric machines, permanent magnet machines stand out as the optimal choices on account of their notable advantages in terms of elevated torque density and efficiency. Nevertheless, the conventional PMSMs cannot fulfill the demanding field weakening requirements of traction applications. Meanwhile it can be alleviated through wound rotor synchronous machines and hybrid excited machines with sacrifice of working efficiency. Nevertheless, VFM machines can achieve desirable field weakening performance with neglectable excitation loss and reduced usage of rare-earth PM material. Therefore, VFM machines exhibit essentially high efficiency along wide speed range and are acknowledged as the most favorable candidate for energy-efficient traction electrification. Despite high torque production and field weakening capability, it is found that the existing VFM machines are subject to inherently contradictory issue between torque production and flux regulation capability, low space utilization ratio, and low cost-effectiveness. This indicates the research directions of the following chapters. A novel hybrid-magnet variable flux memory machine (VFMM) with improved field regulation capability is investigated in Chapter 3. Dual arrangements of permanent magnets (PMs), i.e., high-energy-density neodymium-iron-boron PM and low coercive force (LCF) PM, are arranged in delta array to enhance the capacity for field regulation and boost torque density. The presented machine's topology, essential features, and operating principle are showcased. Utilizing a simplified magnetic circuit model, the qualitative exploration of the foundational design tradeoffs of the machine under consideration is unveiled. The nonlinear magnetic circuit model of the presented machine taking saturation and hybrid-magnet leakage flux into consideration is built for machine analysis. Electromagnetic performance comparisons are carried out by finite element analysis between the presented VFMM and the existing VFMM. The results show the presented machine can achieve significantly improved flux regulation capability while maintain the high output torque due to improved arrangement of hybrid magnetic branches and enhanced flux concentration effect. Finally, the investigated VFMM is prototyped. The operating principle and predicted results are verified by experimental results. To solve the spatial confliction of conventional memory motors, a novel memory motor drive with integrated winding concept is investigated in Chapter 4. The key feature of the proposed idea is to integrate the excitation winding with armature winding, and hence eliminating additional magnetization winding to achieve online magnetization-state regulations. Hence, the spatial confliction of conventional memory motors can be solved. Upon implantation of the proposed design, the winding utilization, torque/power density and fault tolerant capability are significantly improved. In accordance with the field modulation theory, the air-gap flux densities under different magnetization states are derived quantitatively to provide design guideline in initial stage. The integrated memory motor drive is presented systematically to consolidate the field and armature windings. To illustrate the effectiveness of the proposed design, two other conventional memory motors are included for comparisons. It is revealed the presented memory motor with integrated winding concept exhibits 28% higher winding utilization, 43% higher torque/power density and 218% higher flux regulation capability than its counterpart with conventional separate windings. In addition, fault tolerant capability can be significantly improved by integrated design. Finally, a prototype is fabricated, and the experimental measurements are carried out to verify the presented concepts. Chapter 5 provides a comprehensive comparative analysis of doubly salient variable flux memory machines. This analysis encompasses separate and integrated winding structures, covering machine topologies, motor drives, theoretical principles, quantitative performance comparisons, and experimental measurements. Variable flux machine employs field excitation to regulate the magnetic flux and armature excitation to transmit electromagnetic torque, being promising for emerging variable speed applications. The separate winding structure possess inherently de-coupled motor drive, whereas the integrated counterpart exhibits the benefit of better slot spatial utilization. Depending on the simplified equivalent magnetic circuit model, the underlying design guidelines of VFM machines with both separate and integrated winding structures are revealed. Then the lumped nonlinear magnetic circuit models are established and the hybrid permanent magnet (PM) composition ratios of the two types of machines are investigated correspondingly. The comparative results show that the VFM machine with separate winding structure exhibits better field weakening performance, lower interturn short circuit current, larger extension of high efficiency region to high-speed range, whereas the integrated counterpart exhibits higher torque/power density and lower phase cross-coupling. Finally, two prototypes with separate and integrated winding structures are manufactured and measured to verify the presented designs and comparisons. Design and analysis of a memory machine with asymmetric delta-array arrangement for energy-efficient vehicular applications is investigated in Chapter 6. When contrasted with conventional memory machines, the showcased machine attains not only heightened torque/power density but also enhanced flux regulation capability. The underlying design guidelines are revealed according to the equivalent magnetic circuit model qualitatively. Moreover, the dimensional ratios of hybrid magnets are investigated based on the established non-linear asymmetric magnetic circuit model accounting for slotting effect to assess the air-gap flux density and flux regulation capability simultaneously. The presented machine inherently exhibits low-coupling between the armature fields and low-coercive-force magnet and provides desirable demagnetization withstanding capability during variable flux operations. Genetic algorithm oriented multi-objective optimization has been conducted to systematically optimize the presented machine in comparison with two conventional motors, i.e., the existing memory motor and equivalent 10-rotor-pole memory motor. Finally, the presented prototype is fabricated, and dynamic experiments are carried out to verify the theoretical analysis and simulations. In Chapter 7, a demonstration of VFM machine is designed based on the solutions proposed in Chapter 3 to Chapter 6. The practical value and market potential of the developed VFM machine are objectively evaluated, so as to indicate the future research directions for VFM machines. The performance of existing high performance VFM machines is reviewed, which serves as the benchmark for evaluating the developed VFM machine. It is found that i) contradiction between torque/power density and flux regulation capability; ii) low space utilization and low power issue are the main problems that restrict practical applications for VFM machines. The performance of the proposed VFM machine is compared with the conventional high performance VFM machines. Comparison results reveal that the proposed VFM machine exhibit improved torque capability and improved flux regulation capability at the same time. Moreover, the fault tolerant capability and demagnetization withstanding capability under overloading conditions are improved for VFM machines. Furthermore, enhanced flux regulation capability can yield additional reductions in iron loss and eddy current loss, extending the high-efficiency range during high-speed cruising. It is worth noting that the aforementioned superior characteristics make the proposed VFM machine a promising candidate for energy-efficient traction electrification applications. Finally, the research work presented in this thesis is summarized in Chapter 8. It can be concluded that the existing issues of VFM machines, i.e., inherently contradictory issue between torque production and flux regulation capability, low space utilization ratio, and low cost-effectiveness, are effectively resolved by the solutions investigated in Chapter 3 to Chapter 6. Based on the preliminary research work and comparison results, several potential future research directions are discussed, including employing advanced winding arrangement to ease de-/re-magnetization, building full-scale prototype to verify industry-level performances, enhancing fault tolerant capability for VFM machines, and developing advanced control strategy to improve dynamic performances of VFM machines.